2016
DOI: 10.1051/matecconf/20167201092
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Numerical Characterization of the Thermal Physical Properties of Carbon Ceramic Material

Abstract: Abstract.The article presents models representative volume element of the porous carbon-ceramic material. Simulating of heat transfer process in a representative volume element is carried out and thermal characteristics of material are determined by a settlement way. Influence of characteristics of material structure -its porosity and type of reinforcement -on values of heat-physical characteristics is investigated. It is shown that in the field of high temperatures (more than 1500 T) the defining role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It was assumed that all the fibres had equal diameter. The study in [5] demonstrated the evident relationship of the effective and molecular thermal conductivity from the temperature and porosity.…”
Section: Figmentioning
confidence: 86%
See 4 more Smart Citations
“…It was assumed that all the fibres had equal diameter. The study in [5] demonstrated the evident relationship of the effective and molecular thermal conductivity from the temperature and porosity.…”
Section: Figmentioning
confidence: 86%
“…3-4) are presented. It is evident that the material structure is significantly different from the models used in [5]. Fig 3. 3D structure model of a porous CCCM sample area, obtained with X-ray micro-CT scanning.…”
Section: Porous Cccm Structure Investigationmentioning
confidence: 92%
See 3 more Smart Citations